A Sociolinguistics Analysis of Address Terms in Sasak Language - Rajabul, Moh. Gufron (Deskripsi Bahasa, 2023)
This research falls under the broad category of linguistics, i.e., sociolinguistics, which investigates the relationship between language and society. The objective of this research is to examine the sociolinguistic phenomenon known as "address terms" as performed by the native speakers of the Sasak language. This research employed a mix of descriptive, qualitative, and quantitative methods to describe a social phenomenon that occurs in the midst of society and is closely related to the address terms used by native Sasak speakers on Lombok Island. The data displayed in this research are the results of classified participatory and non-participatory observations, in-depth interviews, and online questionnaires. Based on the results of the findings and discussions, the researcher found several conditions. First, the address terms of native Sasak speakers are divided into eight patterns: 1. the nobility pattern; 2. the general pattern; 3. the intimacy pattern; 4. the borrowing pattern; 5. the kinship pattern; 6. the religious pattern; 7. the cultural pattern; and 8. the personal pronoun pattern. Secondly, the address terms serve the following functions: 1. to demonstrate intimacy; 2. to draw attention; 3. to demonstrate politeness; 4. to reflect identity; and 5. to demonstrate power differential. And last, the social factors affecting the use of address terms are: 1. social status; 2. age; 3. family relationship; 4. occupational hierarchy; and 5. degree of intimacy.